The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/mcb.00150-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Accurate Translation Initiation Directed by TISU Involves RPS3 and RPS10e Binding and Differential Eukaryotic Initiation Factor 1A Regulation

Abstract: Canonical translation initiation involves ribosomal scanning, but short 5= untranslated region (5=UTR) mRNAs are translated in a scanning-independent manner. The extent and mechanism of scanning-independent translation are not fully understood. Here we report that short 5=UTR mRNAs constitute a substantial fraction of the translatome. Short 5=UTR mRNAs are enriched with TISU (translation initiator of short 5=UTR), a 12-nucleotide element directing efficient scanning-independent translation. Comprehensive mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
(49 reference statements)
1
44
0
Order By: Relevance
“…In the PIC, eIF1A is located near A-site ribosomal proteins Rps3 and Rps10 and the mRNA channel (20). Both ribosomal proteins contact AUG downstream nucleotides and are implicated in scanning arrest of short 5= UTR mRNAs bearing the translation initiator of short 5' UTR (TISU) element (5). In addition, Rps3 and Rps10 were shown to interact with eIF1A in a cell-based split-Renilla assay (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PIC, eIF1A is located near A-site ribosomal proteins Rps3 and Rps10 and the mRNA channel (20). Both ribosomal proteins contact AUG downstream nucleotides and are implicated in scanning arrest of short 5= UTR mRNAs bearing the translation initiator of short 5' UTR (TISU) element (5). In addition, Rps3 and Rps10 were shown to interact with eIF1A in a cell-based split-Renilla assay (5).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the two tails of eIF1A play opposing roles in scanning and AUG selection. We have recently shown that the interaction of eIF1A with the 43S subunit is partly mediated by Rps3 and Rps10, which are ribosomal proteins located at the A site and which undergo a conformational change during the transition of the 43S to the 80S subunit (5). How these interactions contribute to the initiation process is presently unknown.…”
mentioning
confidence: 99%
“…This ‘start-snatching’ would require functional start codons extremely close to the 5′ end of cellular mRNAs. Start codons of this sort, referred to as Translation Initiator of Short 5′ UTR (TISU) motifs, have been reported in approximately 4 % of mammalian mRNAs, being particularly common in ‘housekeeping’ genes [1618]. We note that this figure is comparable to the ribosomal density we observed on the 5′ UTRs of viral mRNAs (Fig 1E) and is compatible with the 8 – 10 % of viral cap-snatched leaders which we found to contain AUGs (Fig 2D).…”
Section: Discussionmentioning
confidence: 99%
“…We note that this figure is comparable to the ribosomal density we observed on the 5′ UTRs of viral mRNAs (Fig 1E) and is compatible with the 8 – 10 % of viral cap-snatched leaders which we found to contain AUGs (Fig 2D). TISU motifs are functional within 30 nt of the 5′ cap, including at sites at the extreme end of mRNA with 5’ UTRs as short as 5 nt [1618]. As with other upstream translation sites, TISUs have been proposed to regulate the expression of downstream genes, in response to factors including energy deprivation and the circadian rhythm [4749].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation